Evaluation of Omphalocele Treatment Using New Surgical Technique - Askarpour, Shahnam; Peyvasteh, Mehran; Sadeghi, Alireza; Javaherizadeh, Hazhir (Iranian Journal of Pediatric Surgery, 2021)
Introduction: The aim of this study was to evaluate a new technique for treatment of omphalocele using mesh fixation to skin with preserved omphalocele sac. Materials and Methods: Chart of patients who treated with mesh fixation were reviewed. Demographic features, mortality and morbidity following treatment were recorded. Results: in the current study 68 patients (f=32, m=36) were included. Of 68 csaes, 44(64.7%) had giant omphalocele. Among all cases, 20(29.4%) had isolated omphalocele. Mortality was 26.5%(18 of 68). Of survived cases, 21(42%) had detached mesh. Adhesion band was seen in 4(8.2%) of cases. Sepsis was seen in 11.8% of the cases. Conclusion: According to the result of the study, suggested technique is promising and had several benefits. Duration of hospital staying, duration of intubation was less than previous techniques